PENGEMBANGAN KAWASAN PESISIR DI KECAMATAN ABELI KOTA KENDARI - Muis Muis; La Sara; Dasmin Sidu (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2015)
This study is aimed to describe development level, the stakeholders perception and strategy of coastal area development. The highest and the lowest of income of community were found at Pudai of 862 070 and Lapulu of 322,317.38 respectively.The Analytical Hierarchy Process (AHP) analisys which is based on individual and collective opinions. The results of combined analysis found that the responsible of the above third aspect is the government (the weight of 0.695), and a row of private (0.220 weight values) and community (weighted value of 0.085). The results of the combined analysis of opinion in the formulation of development strategies in Abeli coastal aquaculture development puts a priority (weighting value 0.627), industry (weighted value 0.182), the development of tourism (weighted value of 0.108) and the container port (the weight 0.083) respectively. Development strategies of coastal villages in Abeli District should be based on observations of the internal conditions, and anticipating external developments. Internal factors include patterns of human resource development, market information, capital resources and investment, investment policy, infrastructure development, capacity building of local institutions and governance, as well as a variety of collaboration and partnership, while external factors include the gap of problem areas and capacity building of regional autonomy, free trade and regional autonomy.